2006
DOI: 10.1038/sj.cdd.4401879
|View full text |Cite
|
Sign up to set email alerts
|

Neural precursor cells possess multiple p53-dependent apoptotic pathways

Abstract: Neural precursor cells (NPCs) are markedly sensitive to apoptotic insults. p53-dependent transcriptional activation of proapoptotic genes has been hypothesized to regulate NPC death in response to DNA damage. Recent studies of nonNPCs have also indicated that p53 may directly interact with Bcl-2 molecules and thereby regulate death independently of transcription. The contribution of transcription-independent p53 activation in NPC death has not been characterized. In this study, we found that apoptosis caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…Furthermore, cells deficient in Bax or Puma were significantly more resistant to low dose LDM, which is well in line with several other reports showing that p53-mediated Puma, Bax and Bak influence the sensitivity of tumors cells towards various stimuli. [46][47] Although Bcl-2 is reported to be repressed by p53, our results showed that the Bcl-2 expression level remains unchanged irrespective of p53 activation, and exogenous overexpression of Bcl-2 only partially blocked the sensitivity of HCT116 p53 wt cells to 10 nM LDM induced cytotoxicity, indicating that the transcriptional activation rather than repression function of p53 might play a major role in LDM induced apoptotic pathway. 48 The activation of mitochondria by low dose LDM can be further supported by the disruption of DFm and subsequent activation of caspase-9, 3, 6, 7 and PARP (Fig.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, cells deficient in Bax or Puma were significantly more resistant to low dose LDM, which is well in line with several other reports showing that p53-mediated Puma, Bax and Bak influence the sensitivity of tumors cells towards various stimuli. [46][47] Although Bcl-2 is reported to be repressed by p53, our results showed that the Bcl-2 expression level remains unchanged irrespective of p53 activation, and exogenous overexpression of Bcl-2 only partially blocked the sensitivity of HCT116 p53 wt cells to 10 nM LDM induced cytotoxicity, indicating that the transcriptional activation rather than repression function of p53 might play a major role in LDM induced apoptotic pathway. 48 The activation of mitochondria by low dose LDM can be further supported by the disruption of DFm and subsequent activation of caspase-9, 3, 6, 7 and PARP (Fig.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 60%
“…The activation of caspases could be resulted from activation of p53, which usually serves as an upstream regulator. 46 However, a minor p53-independent caspases actviation was observed under the same experimental treatment. This might be possibly explained by the direct activation of mitochondria by this enediyne compound, as illustrated by another enediyne antibiotic calicheamicin whose induction of apoptosis proceeds through a caspase-mediated mitochondria amplification loop regardless of p53 status.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%
“…p53 is a major regulator of developmental and DNA damage-induced apoptosis during embryogenesis (Armstrong et al 1995;Sah et al 1995;Komarova et al 1997;Frenkel et al 1999) and in neural precursor cells of the developing central nervous system (CNS) (Akhtar et al 2006;Geng et al 2007). In the adult brain, p53 controls self-renewal of adult neural stem cells (Meletis et al 2006;Gil-Perotin et al 2006), and loss of p53 leads to expansion of the stem cell/progenitor compartment (GilPerotin et al 2006).…”
Section: P53 and Pathologies Associated With Acute Ischemiamentioning
confidence: 99%
“…43 Noxa is upregulated in many cell types including neural precursor cells and neurons from stimuli that induce its p53-dependent transcription and resultant apoptosis, whereas Noxa deficiency prevents p53-dependent apoptosis. 27,[43][44][45][46] Puma was identified via cloning in simultaneous reports. 28,47 Puma-deficient mice appear normal throughout development and do not have any obvious neuronal abnormalities.…”
Section: Proapoptotic Bh3 Domain-only Subgroup: From Rheostat To Reamentioning
confidence: 99%